Questões envolvidas no uso de tecnologias do ensino pela análise do comportamento - Azoubel, Marcos Spector (2014)
There are many behavior analysts studies about education. Based on these research findings, methods were developed to use of the knowledge produced on behavior in educational contexts. Though they have demonstrated efficacy through a wide range of empirical research, the area s teaching procedures are underutilized. Several causes for such disuse are pointed out, most of them with respect to preconceptions, ignorance or rejection of the area s proposals. The aim of this study is to investigate possible variables involved in the use of teaching methods derived from the Behavior Analysis. For this study five behavior analysts, with experience in the supervision of theses and / or dissertations on education and Behavior Analysis and teaching in graduate programs, were interviewed. Finally, the obstacles mentioned by the literature with those reported by the professionals were compared. Results shows that, for attendees, most of the obstacles for using the approach s teaching methods relates to problems inherent to its technology and Behavior Analysis community itself. Therefore, it is placed into question the arguments pointing out misconceptions, ignorance and disagreements as the major cause for the underutilization of behavior analysis' teaching procedures